Rpv3-1 mediated resistance to grapevine downy mildew is associated with specific host transcriptional responses and the accumulation of stilbenes - Eisenmann, Birgit; Czemmel, Stefan; Ziegler, Tobias; Buchholz, Günther; Kortekamp, Andreas; Trapp, Oliver; Rausch, Thomas; Dry, Ian; Bogs, Jochen (BMC plant biology, 2019)
European grapevine cultivars (Vitis vinifera spp.) are highly susceptible to the downy mildew pathogen Plasmopara viticola. Breeding of resistant V. vinifera cultivars is a promising strategy to reduce the impact of disease management. Most cultivars that have been bred for resistance to downy mildew, rely on resistance mediated by the Rpv3 (Resistance to P. viticola) locus. However, despite the extensive use of this locus, little is known about the mechanism of Rpv3-mediated resistance.